Formulasi dan Uji Aktivitas Antibakteri Sediaan Gel Ekstrak Buah Murbei Hitam (Morus nigra L.) sebagai Antijerawat - Yola Desnera Putri; Susi Sulastri; Deby Tristiyanti; Adit Andriyannto (Journal of Pharmaceutical and Sciences, 2026)
Acne is one of the most common skin disorders affecting various age groups, particularly adolescents, and is caused by inflammation of the pilosebaceous follicles associated with bacterial proliferation. The primary bacteria involved in acne pathogenesis are Propionibacterium acnes (P. acnes) and Staphylococcus epidermidis (S. epidermidis). This study aimed to formulate an anti-acne gel containing ethanol extract of black mulberry (Morus nigra L.) fruit and to evaluate its antibacterial activity. The black mulberry fruit was extracted by maceration using 96% ethanol. The resulting extract was formulated into a Carbopol 940-based gel at three different concentrations: 1.25% (F1), 2.5% (F2), and 5% (F3). The formulated gels were evaluated for organoleptic properties, homogeneity, pH, viscosity, spreadability, antibacterial activity using the agar well diffusion method, and skin irritation using the Draize method. The results showed that the ethanol extract of black mulberry fruit exhibited antibacterial activity against P. acnes and S. epidermidis, with inhibition zone diameters of 12.0 ± 0.90 mm and 12.8 ± 0.59 mm, respectively, at a concentration of 1.25%, indicating strong antibacterial activity. After formulation into a gel, the highest antibacterial activity was observed in Formula 3 (F3) after 28 days of storage, with inhibition zone diameters of 15.1 ± 0.06 mm against P. acnes and 15.3 ± 0.10 mm against S. epidermidis. All formulations met the required physical evaluation parameters and showed no signs of irritation in a preliminary Draize irritation test during the observation period. Therefore, the ethanol extract of black mulberry fruit has the potential to be developed as a topical anti-acne gel with antibacterial activity against P. acnes and S. epidermidis.